THE CREDITOR AS PARTICIPANT IN INSOLVENCY PROCEEDINGS - Anca Roxana ADAM (Challenges of the Knowledge Society)
A creditor is the party who, within a binding judicial relationship, has a claim on the services of giving, doing or not doing of the second party, called debtor. In insolvency a creditor is an individual or a legal entity that is entitled to claim payment of an amount of money by the debtor, in relation to whom the creditor holds an uncontested, liquid and enforceable claim. Insolvency Law no. 85/2006 defines the concept of creditors entitled to request initiation of the insolvency proceedings, as well as the concept of creditors entitled to participate in the insolvency proceedings. Aim of this study is an in-depth analysis of the two categories of creditors and the requirements for holding this quality.